The Influence of Prices and Advertising on Decisions Purchase Oppo Smartphones at Imelda Teluk Phones in South Nias - Berkati Halawa (Journal of General Education Science, 2024)
Android-based smartphones are a very effective and efficient digital technology communication tool that is really needed by the public in carrying out their mobility and activities in the digital economy. The Oppo smartphone is already widely known among the public. This research aims to analyze the influence of price and advertising on purchasing decisions for Oppo smartphone products at Imelda Mobile Telukdalam South Nias. This research is quantitative descriptive research using manual data obtained incidentally (accidental slice) and analyzed using validity test methods, reliability tests, classical assumption tests, multiple linear regression analysis, and hypothesis analysis. The results of the research show that price has no effect on purchasing decisions with a value of tcount<ttable or 0.978<1.980, while advertising has a positive and significant effect on purchasing decisions as indicated by a value of tcount>ttable or 2.173>1.980. Simultaneously price and advertising have a significant positive influence on purchasing decisions. with a value of Fcount> Ftable or 4.506> 3.07. Thus, many people make purchases of Oppo smartphone products.